2014
DOI: 10.1152/jn.00058.2014
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic plasticity induced by brief activity deprivation enhances long-term potentiation in the mature rat hippocampus

Abstract: Félix-Oliveira A, Dias RB, Colino-Oliveira M, Rombo DM, Sebastião AM. Homeostatic plasticity induced by brief activity deprivation enhances long-term potentiation in the mature rat hippocampus. J Neurophysiol 112: 3012-3022, 2014. First published September 10, 2014; doi:10.1152/jn.00058.2014.-Different forms of plasticity occur concomitantly in the nervous system. Whereas homeostatic plasticity monitors and maintains neuronal activity within a functional range, Hebbian changes such as long-term potentiation (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
0
18
1
Order By: Relevance
“…For example, it has been shown in mice that retinal silencing with TTX can promote bursting in the LGN (41) and burst stimulation of the geniculate can potentiate VEPs (59). Homeostatic adaptations that facilitate experience-dependent synaptic potentiation (24,60,61), such as reduced cortical inhibition and alterations in the properties of NMDA receptors (62-64), could also contribute to the therapeutic effects of retinal inactivation. We are encouraged to believe that the approach described here, and/or the knowledge gained by studying it, might ultimately have therapeutic potential for the treatment of amblyopia and other types of neurological rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown in mice that retinal silencing with TTX can promote bursting in the LGN (41) and burst stimulation of the geniculate can potentiate VEPs (59). Homeostatic adaptations that facilitate experience-dependent synaptic potentiation (24,60,61), such as reduced cortical inhibition and alterations in the properties of NMDA receptors (62-64), could also contribute to the therapeutic effects of retinal inactivation. We are encouraged to believe that the approach described here, and/or the knowledge gained by studying it, might ultimately have therapeutic potential for the treatment of amblyopia and other types of neurological rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…These silent synapses could later be 'unsilenced' or reactivated so as to permit subsequent, greatly enhanced levels of long-term potentiation (LTP) [69]. Another study using acute hippocampal slices showed similarly enhanced LTP after 3 h of TTX and APV (an NMDA receptor blocker) treatment [70]. Importantly, in vivo studies using sensory deprivation paradigms demonstrated that visual deprivation (i.e.…”
Section: Cellular and Molecular Mechanisms: Overlapping And Distinct mentioning
confidence: 99%
“…Moreover, following acoustic overexposure, fusiform cells that showed hyperactivity also exhibited a change in the firing pattern from regular spiking to bursting activity, a change that was mediated by a down regulation of high voltage activated potassium channels (Pilati et al, 2012). Because induction of LTP/LTD may depend on the cell’s intrinsic excitability (Felix-Oliveira et al, 2014), it is possible that such changes could contribute to the observed alterations in STDP plasticity following noise exposure and tinnitus.…”
Section: Multisensory Mechanisms In Cn and Their Contribution To Tmentioning
confidence: 99%